2018
DOI: 10.1039/c8cp00808f
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/ZnO van der Waals heterostructure as a high-efficiency water splitting photocatalyst: a first-principles study

Abstract: Previous investigations [H. L. Zhuang and R. G. Hennig, J. Phys. Chem. C, 2013, 117, 20440-20445; J. Kang, S. Tongay, J. Zhou, J. Li and J. Wu, Appl. Phys. Lett., 2013, 102, 012111] demonstrated that molybdenum disulfide (MoS2) is a potential photocatalyst for water splitting. However, the photogenerated electron-hole pairs in MoS2 remain in the same spatial regions, resulting in a high rate of recombination. Using first-principles calculations, we designed a MoS2-based heterostructure by stacking MoS2 on two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
139
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(173 citation statements)
references
References 67 publications
16
139
0
1
Order By: Relevance
“…They all are the macroscopic phenomena of electron transitions between energy bands in solid under the perturbation of photoelectric magnetic eld. 57 Obviously, at both the X and Y directions the dielectric peaks are in the visible range, while at the Z direction the dielectric peak is in the ultraviolet region. The calculation of the imaginary part of the dielectric constant 3 2 of the HfS 2 /MoTe 2 multilayer heterostructure as a function of energy is illustrated in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They all are the macroscopic phenomena of electron transitions between energy bands in solid under the perturbation of photoelectric magnetic eld. 57 Obviously, at both the X and Y directions the dielectric peaks are in the visible range, while at the Z direction the dielectric peak is in the ultraviolet region. The calculation of the imaginary part of the dielectric constant 3 2 of the HfS 2 /MoTe 2 multilayer heterostructure as a function of energy is illustrated in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Since materials with type-II heterostructure alignment are regarded to make hole-electron separation more efficient, and can be used for optical absorption in a wider range of solar spectra, 53,57 in order to reveal the unique characteristics of HfS 2 / MoTe 2 , a detailed discussion of its imaginary part of the dielectric constant 3 2 for light absorption is given. In the linear response range, the complex dielectric response function to describe the optical properties of a material is 3 ¼ 3 1 + i3 2 , where 3 1 denotes the real part calculated by the well-known Kramers-Kronig relation and 3 2 is the imaginary part obtained from the matrix elements of the wave function for occupied and nonoccupied states.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Many strategies have been put in place to advance "green" technologies, and the development of photocatalysts for water splitting is considered to be a promising measure because these catalysts can break down water into hydrogen (H 2 ) and oxygen (O 2 ) under the illumination of visible light to produce sustainable and renewable energy. 1 As photoelectrochemical (PEC) water splitting by semiconductors attracts more and more attention, [2][3][4][5] it has been reported that a crucial requirement for water splitting is a suitable band edge of the semiconductor, 1,6 where the conductionband minimum (CBM) of the material should be greater than the reduction potential (À4.44 eV) for H + /H 2 , and the valenceband maximum (VBM) of the material should be less than the oxidation potential (À5.67 eV) for O 2 /H 2 O, 7 which means the bandgap of any qualied photocatalyst should be more than 1.23 eV. 8 Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rapid recombination of photo-induced pairs of electron-hole in the photocatalytic reaction would cause a reduction in its efficiency. The previous studies showed that coupling this semiconductor with a narrow bandgap semiconductor has resulted in an improvement in its light absorption range and yielded better catalytic results [33][34][35][36][37][38][39][40] . For instance, Tan et al reported that incorporation of ZnO into MoS 2 could result in easy transfer of electrons to the ZnO surface.…”
mentioning
confidence: 99%